C‐Kit Mutation and Localization Status as Response Predictors in Mast Cell Tumors in Dogs Treated with Prednisone and Toceranib or Vinblastine. (30th November 2017) - Weishaar, K.M.; Ehrhart, E.J.; Avery, A.C.; Charles, J.B.; Elmslie, R.E.; Vail, D.M.; London, C.A.; Clifford, C.A.; Eickhoff, J.C.; Thamm, D.H.
Abstract : Background: KIT inhibitors, such as toceranib (TOC), and vinblastine (VBL) have not been prospectively compared in the treatment of macroscopic mast cell tumors (MCTs). Also, it is unknown whether VBL or TOC is superior for treating MCT without c‐kit mutations. Hypothesis/Objectives: To determine the value of KIT genotyping and localization in treatment decisions for dogs with macroscopic MCT. We hypothesized that c‐kit mutated MCT would have a better response to TOC than VBL. Animals: Eighty‐eight client‐owned dogs with macroscopic MCT. Methods: Prospective, randomized trial. Dogs were randomized to TOC (2.75 mg/kg EOD) or VBL (2.5 mg/m 2 weekly × 4 then EOW) by KIT localization and c‐kit mutation status using an adaptive randomization scheme. Results: Sixty dogs were allocated to TOC and 28 to VBL. Of the dogs receiving TOC, 20% had c‐kit mutations, compared to 30% receiving VBL ( P = 0.74). Overall response rates were 46% (TOC) and 30% (VBL) (odds ratio = 1.56 [0.62–3.92]; P = 0.28). Median progression‐free survival (PFS) for dogs receiving VBL was 78 days (7–1, 521) and for TOC 95.5 (14–990); hazard ratio (HR) = 1.34 [0.72–2.50]; P = 0.36. Median overall survival (OS) was 241.5 days (10–1, 521) for the VBL group and 159 (20–990) for the TOC group; HR = 0.80 ([0.45–1.41]; P = 0.44). Conclusions and Clinical Importance: Neither PFS nor OS was significantly different between treatment groups. As the proportion of dogs with c‐kit mutations was not different between treatment groups in this population of dogs, c‐kit mutation status did not predict treatment response.